A unified secondary electron cut-off presentation and common mistakes in photoelectron spectroscopy. (1st December 2022) - Schultz, Thorsten
Abstract: Photoelectron spectroscopy is a powerful surface analysis technique that can differentiate different bonding environments and directly determine the absolute work function of a sample. Despite its ever-easier accessibility—or perhaps precisely because of it—some common mistakes or bad habits are often found in the literature when it comes to the evaluation or presentation of photoelectron spectroscopy data. Here we address some of these issues and give suggestions for best practice, i.e., a proper presentation of the secondary electron cut-off used for work function determination, correct binding energy referencing and some tips for appropriate peak fitting, as well as valuable literature references to more detailed tutorials. Finally, we present a concise step-by-step guide on how to conduct a complete x-ray photoelectron spectroscopy analysis of an unknown sample.